Mysteries of CADASIL – the contribution of neuropathology to understanding of the disease - Dziewulska, Dorota (Folia Neuropathologica, 2009)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a systemic vascular disease characterized by impairment of vascular smooth muscle cell (VSMC) structure and function related to NOTCH 3 mutations. Clinically the syndrome is manifested as recurrent ischaemic strokes, migraine with aura, dementia and psychiatric symptoms. In spite of intensive investigations, there is relatively little insight into the underlying pathomechanisms that link VSMC with the Notch 3 signalling pathway, morphological changes and clinical symptoms. The introduction into neuropathology of novel immunohistochemical and molecular techniques opened new research and diagnostic perspectives in CADASIL studies. We present a review of current concepts regarding CADASIL pathogenesis, clinical picture and diagnosis in which neuropathological examinations played a key role.